Behavior of consumers of clothing made of eco-materials in the European Union, the USA and Ukraine - Man, Mariann; Tkachov, M. M. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The results of the study signal an increased level of demand for clothing made from sustainable materials among people who are aware of the dangers of textile production or support the environmental movement. To stimulate the consumption of eco-friendly clothing among other consumers, companies need to create an information field that demonstrates the efficiency of consumption of clothes made from eco-friendly fabrics compared to the mass market. In the studied regions, consumers are ready to spend more on the purchase of environmentally friendly materials if they understand that their actions really help the environment.
Поведінка споживачів одягу з екоматеріалів в Європейському Союзі, США та Україні
Keywords: market; demand; supply; clothing; environmental materials; efficiency; enterprises